Reaksi Pasar Modal Atas Pengumuman Terpilihnya Presiden Amerika Serikat Joe Biden (Event Study Pada Indeks LQ45 Tahun 2020) - Putu Adi Pratama; Sunitha Devi (Universitas Pendidikan Ganesha, 2021)
This research is a quantitative study that aims to determine the difference average abnormal return and trading volume activity before and after the announcement of the selected United States President Joe Biden. This research was conducted in 7 days. Population and sample of the research are the LQ45 index. The sample selection method used is purposive sampling technique with certain criteria. Data testing techniques used are paired sample t-test and Wilcoxon signed ranks test. The results of this research shows that there are not significant differences in the average abnormal return and trading volume activity before and after announcement of the selected United States President Joe Biden.